A molecular phylogeny of the genus Psittacula sensu lato (Aves: Psittaciformes: Psittacidae: Psittacula, Psittinus, Tanygnathus, †Mascarinus) with taxonomic implications - Braun, Michael P.; Datzmann, Thomas; Arndt, Thomas; Reinschmidt, Matthias; Schnitker, Heinz; Bahr, Norbert; Sauer-Gürth, Hedwig; Wink, Michael (Zootaxa, 2019)
The long-tailed parakeets of the genus Psittacula Cuvier, 1800 have thus far been regarded as a homogeneous and monophyletic group of parrots. We used nucleotide sequences of two genetic markers (mitochondrial CYTB, nuclear RAG-1) to reconstruct the phylogenetic relationships of Psittacula and closely related species. We found that the Asian genus Psittacula is apparently paraphyletic because two genera of short-tailed parrots, Psittinus Blyth, 1842 and Tanygnathus Wagler, 1832, cluster within Psittacula, as does †Mascarinus Lesson, 1830. To create monophyletic genera, we propose recognition of the following genera: Himalayapsitta Braun, 2016 for P. himalayana, P. finschii, P. roseata, and P. cyanocephala; Nicopsitta Braun, 2016 for P. columboides and P. calthrapae; Belocercus S. Müller, 1847 for P. longicauda; Psittacula Cuvier, 1800 for P. alexandri and P. derbiana; Palaeornis Vigors, 1825 for †P. wardi and P. eupatria; and Alexandrinus Braun, 2016 for P. krameri, †P. exsul, and P. (eques) echo. Additionally, Psittacula krameri and P. alexandri are paraphyletic species, which should be split to form monophyletic species.